PENINGKATAN LITERASI KESEHATAN MENTAL REMAJA MELALUI MEDIA KREATIF DI SMPN 11 SAMARINDA - Lujeng Rahayu Anggraini; Sarasmawati; Nabila Noor Alifa Basuki (STKIP Subang, 2025)
Mental health is a crucial aspect of student development, yet it is often overlooked in schools. Adolescents are vulnerable to academic, social, and emotional stress, requiring appropriate interventions to increase their awareness and ability to maintain their mental health. This study aims to improve adolescent mental health literacy through the use of creative media in the Leadership Project